You, Inc. : the art of selling yourself - Beckwith, Harry, 1949- (HighBridge Co., 2007)
Written in a personable and homespun style, You, Inc. offers doses of humor and pithy knowledge to anyone who wants to thrive in the increasingly competitive business world. What veteran sales and marketing experts Harry and Christine Beckwith understand is that, to succeed in life, the most important thing you need to be able to sell is YOU--whether it's in a job interview, a social gathering, or during a business negotiation. The Beckwiths provide a treasure trove of insights and tips to help you present yourself credibly, confidently, and comfortably.